2001
DOI: 10.1128/jb.183.15.4609-4613.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Staphylococcus aureus Type 5 and Type 8 Capsular Polysaccharides by CO 2

Abstract: Staphylococcus aureus expression of capsular polysaccharide type 5 (CP5) has been shown to be downregulated by CO 2 . Here we show that CO 2 reduces CP5 expression at the transcriptional level and that CO 2 regulates CP8 expression depending on the genetic background of the strains. Growth in the presence of air supplemented with 5% CO 2 caused a significant decrease in CP8 expression in four S. aureus strains, a marginal effect in four strains, and higher CP8 expression in strain Becker. Absolute CP8 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
(22 reference statements)
2
26
1
Order By: Relevance
“…Since the sequences of the promoter regions of the cap5 and cap8 operons are almost identical (38), it is not surprising that CP5 and CP8 are regulated similarly. However, it has been reported that microcapsules could be regulated differently by carbon dioxide depending on the strain being studied (15).…”
Section: Discussionmentioning
confidence: 99%
“…Since the sequences of the promoter regions of the cap5 and cap8 operons are almost identical (38), it is not surprising that CP5 and CP8 are regulated similarly. However, it has been reported that microcapsules could be regulated differently by carbon dioxide depending on the strain being studied (15).…”
Section: Discussionmentioning
confidence: 99%
“…The reporter plasmid pSN8388 (carrying the cap5 promoter fused to the promoterless reporter gene xylE in pCL4 [18]) was transduced from strain Newman into the isogenic sae mutant of strain Newman by using 11. The presence of correct constructs was confirmed by restriction mapping of the isolated plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Several virulence genes are also regulated in response to C i availability. CO 2 /bicarbonate is likely to be a physiologically significant signal encountered by pathogens in the host environment (Drysdale et al, 2005;Herbert et al, 2001;Koehler, 2002;Hyde et al, 2007). C i -responding regulation is not restricted to carbon assimilation or virulence genes.…”
Section: Introductionmentioning
confidence: 99%